(untitled) (Washington, D.C., 2007)
Shah (public sector governance, World Bank Institute) brings together learning modules on local financial management prepared for World Bank Institute learning programs over the past three years. Contributors in accounting, public policy, political science, and economics provide an overview of local government financial accounting and reporting, document better practices in cash management, and explain how to use transparent procurement processes to mitigate corruption. Practical guidance is given on using and assessing debt, managing debt, and detecting corruption. The book is a collaborative effort of the Swedish International Development Cooperation Agency and the World Bank Institute to support reform of the public expenditure management and financial accountability systems of developing countries, especially in Africa.
Keywords: Local finance.,Finance, Public